Cross-cultural service management for international medical students in China: developing a conceptual framework / Pengfei Qiu ... [et al.] - Pengfei, Qiu; Boo, Ho Voon; Yacob, Yusman; Shan, Bin (UiTM Cawangan Kedah, 2022)
In the era of globalization, the internationalization of higher education has become a worldwide trend. The cross-cultural management service for Chinese international students is still in the exploratory stage. The management system and management methods still need to be improved. In particular, international medical students have special needs in service management. The current service management model is very challenging to meet the needs of students. Therefore, it is a vital topic to explore cross-cultural service management strategies suitable for international medical students and improve service management quality. This paper combs the relevant research on cross-cultural adaptability and cross-cultural service management of international students in China. In addition, the dimensions of cross-cultural service management are explored in medical colleges and universities, and the quality and service expectation of cross-cultural management services for international medical students. This paper puts forward suggestions to improve the cross-cultural service management of medical colleges and universities from three levels: government, universities, and students.